1987
DOI: 10.1099/00207713-37-1-4
|View full text |Cite
|
Sign up to set email alerts
|

Genus Erwinia: Numerical Analysis of Phenotypic Features

Abstract: API 20E and API SOCHE systems (72 phenotypic tests) were applied to a total of 529 strains, including 421 strains belonging to 21 different Erwinia species, 66 Enterobacter agglomerans strains, 18 Escherichia adecarboxylata strains, and 24 strains of 16 other enterobacteria. The results were analyzed numerically by using the Gower similarity coefficient and the unweighted average linkage method. The named Erwinia strains were distributed over 27 phena, some of which also contained strains received as Enterobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
74
3
8

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 38 publications
12
74
3
8
Order By: Relevance
“…Thus, our results do not contradict the proposed and generally accepted inclusion of " [Pseudomonas] trifolii" in Erwinia herbicolu (33). Recently, Verdonck et al (56) showed that this strain belongs phenotypically in Erwinia herbicola phenon 9. The position of leaf nodule organism LMG 2806 has been discussed previously in more detail (16).…”
Section: Resultscontrasting
confidence: 44%
“…Thus, our results do not contradict the proposed and generally accepted inclusion of " [Pseudomonas] trifolii" in Erwinia herbicolu (33). Recently, Verdonck et al (56) showed that this strain belongs phenotypically in Erwinia herbicola phenon 9. The position of leaf nodule organism LMG 2806 has been discussed previously in more detail (16).…”
Section: Resultscontrasting
confidence: 44%
“…However, both 16S rRNA gene sequencing and MLSA support the phylogenetic delineation of P. vagans from P. agglomerans. Past studies have highlighted the difficulties in identifying Pantoea strains based on phenotypic data (Beji et al, 1988;Brenner et al, 1984;Mergaert et al, 1984;Verdonck et al, 1987), and it has been suggested that caution be exercised when basing identification solely on commercial phenotypic identification systems (Gavini et al, 1989). Despite the high phenotypic similarity within the genus Pantoea, several biochemical characteristics were recognized that could distinguish the four novel species from each other and from their closest phylogenetic neighbours.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1970s, various attempts have been made to clarify the Erwinia herbicola-Enterobacter agglomerans complex (Ewing & Fife, 1972;Gardner & Kado, 1972;Young et al, 1978;Dye, 1981;Brenner et al, 1984;Verdonck et al, 1987;Beji et al, 1988). The most comprehensive study to date was performed by Brenner et al (1984), who separated 124 strains belonging to this complex into 13 groups based on their DNA-DNA hybridization relatedness.…”
mentioning
confidence: 99%